2013
DOI: 10.1016/j.jenvman.2012.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Why, how, and how far should microbiological contamination in a coastal zone be mitigated? An application of the systems approach to the Thau lagoon (France)

Abstract: This paper describes the building of an integrated simulation tool based on a systems approach, and its contribution to local political discussion of the mitigation of microbiological contamination of the water in a coastal area. Local management schemes view water quality as a high-priority environmental objective. In practice, how far this objective is achieved depends on trade-offs between the costs of improved water treatment facilities and the acceptable impacts of water contamination. An in-the-field exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…support of small pontoons and oyster-production rafts, which alone occupy ca. 20 % of the lagoon surface; Mongruel et al 2013) and were the most common artificial substrate identified in the lagoon, even when excluding oyster-production rafts. Therefore, the elevated colonization of metal structures appears to be associated with their high accessibility.…”
Section: Polyp Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…support of small pontoons and oyster-production rafts, which alone occupy ca. 20 % of the lagoon surface; Mongruel et al 2013) and were the most common artificial substrate identified in the lagoon, even when excluding oyster-production rafts. Therefore, the elevated colonization of metal structures appears to be associated with their high accessibility.…”
Section: Polyp Habitatmentioning
confidence: 99%
“…(Bonnet et al 2012), although the presence of the benthic population still requires further confirmation. Thau lagoon is a semi-enclosed system under heavy human pressure, where shellfish farming is one of the most important economical activities, with a production of 15 000 tons of oysters and mussels per year (Mongruel et al 2013). We here provide a qualitative assessment of the distribution and habitat use of the benthic population of Aurelia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptions, for example, are the simulation tool for water quality management of the Thau Lagoon in France (Mongruel et al, 2013) and the application of the Scheldt nitrogen apportionment model (Vermaat et al, 2012) to estimate off-shore eutrophication (www.iseca.eu). Furthermore, a SAF webgallery has been created for dissemination purposes, making a selection of the models available for downloading (http://www.…”
Section: Component Use and Reuse In Spicosamentioning
confidence: 99%
“…Combining macro-economic and dynamicpollution models of the lagoon at the local level provided an effective, integrated assessment of the risk of microbiological contamination and facilitated the evaluation of scenarios with different local development patterns and management strategies (Mongruel et al 2012).…”
Section: System Thinkingmentioning
confidence: 99%
“…The governance component of the dynamic contamination model for the lagoon was sufficiently flexible to simulate changes in its monitoring system and in the protocols that lead to administrative decisions. This allowed the pollution impact assessment to distinguish clearly between real contamination, observed contamination, and risk management (Mongruel et al 2012).…”
Section: Simulation Analysismentioning
confidence: 99%